Impact of the Digital Economy on International Trade - Ikromjon, Axmedov (International Journal on Integrated Education, 2023)
This article examines the digitalization of international trade processes and the role of relevant technologies in it. The scale of digitalization in the global economy and international trade is growing rapidly, and the digital space is becoming a key area for global trade. In the study, the impact of digitalization on international trade, changes in the composition and form of international trade, increased global competition and its transition to the intangible sphere due to its influence; the emergence of new forms and opportunities for international business through digitalization, the growth of cross-border commerce and the expansion of invisible employment, and the reduction of problems between cross-border and domestic operations are explored in a globalized digital environment.